Acute renal injury due to rhabdomyolysis: A tertiary hospital experience - Arac, Esref; Solmaz, Ihsan; Yuksel, Enver; Ekin, Nazim; Arac, Songul (Annals of Medical Research, 2021)
Aim: Rhabdomyolysis (RML) is a clinical and biochemical syndrome caused by acute necrosis of striated muscle fibers and the subsequent transportation of potentially toxic cellular contents into the systemic circulation. In this study, we present data from rhabdomyolysis patients that developed acute renal failure who were hospitalized and treated in our clinic in 2019. Materials and Methods: We reviewed all cases of RML treated in the tertiary hospital within a 12-month period, which was defined as serum creatinine kinase (CK) levels > five times the upper normal limit. The inclusion criteria were as follow: (a) being aged ≥ 18 years, (b) being treated for RML within the designated time period, (c) AKI development. The exclusion criteria are as follows: (a) being aged 5 time upper normal limit (UNL), 14 conformed to the inclusion criteria and were selected as subjects Results: A total of 14 patients were included in the study, 12 of which were male. The mean age of the patients was 48.1 (18–80). The etiologies were as follows: hypothyroidism, 3; prolonged exposure to sun, 2; electrolyte imbalance due to severe diarrhea, 1; viral upper respiratory tract infection (URTI), 3; intramuscular injection, 1; heavy exercise or falls.Conclusion: Rhabdomyolysis is an interdisciplinary clinical condition that can lead to life-threatening outcomes including AKI. Rapid diagnosis and treatment can be life-saving. AKI is a significant potential complication of RML and renal function should be evaluated irrespective of CK levels or the presence of myoglobinuria.
Keywords: Acute kidney injury; creatininekinase; liver dysfunction; rhabdomyolysis